Potential for controlling Aedes and Culex mosquito larvae by joint action compounds isolated from Boehmeria nivea - Tran, Vy Anh; Thi Vo, Thu-Thao; Van Le, Thi Hong; Le, Nga; Setzer, William N.; Thuong, Vo Thanh; Hung, Nguyen Huy (Industrial crops and products, 2024)
This study evaluates compounds isolated from Boehmeria nivea, identifies the chemical composition, and examines its toxicity to mosquito larvae. Liquid chromatography coupled to a mass spectrometer, as well as 1H and 13C nuclear magnetic resonance spectroscopy, were used to determine the chemical composition. The 3rd instar and early 4th instar larvae of Aedes aegypti, Aedes albopictus, Culex quinquefasciatus and Culex fuscocephala. were used as test subjects for the activity. There are 4 active ingredients extracted from B. nivea including 4-hydroxybenzoic acid, pomolic acid, ursolic acid, and daucosterol that have shown low toxicity to Moina macrocopa (48 h LC50 of 16.34–22.32 µg/mL), against Aedes spp. larvae with 24 h LC50 values between 28.10 and 55.04 µg/mL; against the larvae of Culex spp. with values of 24 h LC50 between 8.0 and 17.66 µg/mL, and have shown synergistic or additive effects at binary combinations. This research opens up potential possibilities for developing environmentally friendly natural compounds that kill mosquito larvae and fight dangerous diseases caused by mosquitoes. [Display omitted] •Main larvicidal compounds against four mosquito species were isolated from Boehmeria nivea root.•Joint actions of larvicidal compounds were evaluated.•Larvicidal compounds were less toxic to plankton (Moina macrocopa).•Fraction containing larvicidal compounds was excellent against Aedes mosquitoes.